Wildlife values and management in northern Sudan - Nimir, Mutasim Bashir, author; Nagy, Julius G., advisor; Young, Robert A. (Robert Alton), 1931-2013, committee member; Decker, Eugene, committee member; Alldredge, A. William, committee member (Colorado State University. Libraries, 1983)
An overview of wildlife resources and wildlife values and management are presented in this study. Information on history of wildlife distribution, wildlife values and management practices have been obtained from writings of early travelers and explorers and government archives. Information on present status of wildlife has come from surveys conducted by the author and other workers during the last 15 years. The Wildlife Administration records were reviewed for information on laws, policies, and records of game license sales and export of wildlife products. The province of Southern Darfur was chosen to develop a case study and to make conclusions which could be applied elsewhere in Northern Sudan. Wildlife has been more abundant in Northern Sudan in the past than it is today. Information on present distribution and abundance of wildlife is very limited. The conservation status in national parks, game reserves and sanctuaries is rated as unsatisfactory. Factors causing losses of wildlife resources are inadequate laws, loss of habitats, lack of qualified personnel, lack of public awareness about wildlife conservation and conflicts in land use planning. Economic values of wildlife are of central importance to the future of wildlife conservation in Northern Sudan. The present economic values of wildlife are related to hunting, trade in wildlife products and wildlife damage to agriculture and livestock. Legal hunting is of limited significance as possession of firearms is restricted by law and wildlife areas are remote from where the majority of the population live. Ivory and reptile skin trade provide considerable revenue. As most of the wildlife products are collected through illegal hunting and traded illegally the economic benefit from wildlife is not appreciated by the government. Wildlife damage to agriculture and livestock is most serious in Southern Darfur where it is mostly caused by baboons and hyenas. Recommendations include that surveys should be conducted to present realistic estimates of wildlife distribution and abundance. Realistic conservation goals should be adopted based on surveys' results. Wildlife conservation should be incorporated in national land use plans. The Wildlife Administration should recruit biologists and relocate its personnel and vehicles closer to wildlife areas. Wildlife programs should be coordinated in Northern and Southern Sudan. New laws should be adopted. The trade in ivory and other wildlife products should be controlled. The Wildlife Administration should monopolize all ivory export and taxes should be increased in export of wildlife products. The Wildlife Administration should be more involved in controlling wildlife damage. Laws should be changed to allow the Wildlife Administration to direct revenue generated from wildlife towards wildlife conservation projects. It is recommended that education in wildlife conservation should be included in school programs and in the Sudanese media.
Keywords: Wildlife conservation -- Sudan; Wildlife management -- Sudan